Palladium-catalyzed synthesis and nucleotide pyrophosphatase inhibition of benzo[4,5]furo[3,2-b]indoles - Do, Hoang Huy; Ullah, Saif; Villinger, Alexander; Lecka, Joanna; Sévigny, Jean; Ehlers, Peter; Iqbal, Jamshed; Langer, Peter (Beilstein Journal of Organic Chemistry, 2019)
A two-step palladium-catalyzed procedure based on Suzuki–Miyaura cross coupling, followed by a double Buchwald–Hartwig reaction, allows for the synthesis of pharmaceutically relevant benzo[4,5]furo[3,2-b]indoles in moderate to very good yield. The synthesized compounds have been analyzed with regard to their inhibitory activity (IC50) of nucleotide pyrophosphatases h-NPP1 and h-NPP3. The activity lies in the nanomolar range. The results were rationalized based on docking studies.
Keywords: Buchwald–Hartwig reaction; cyclization; N-heterocycles; palladium; Suzuki–Miyaura reaction